BAYESIAN ESTIMATION OF PARAMETERS OF INFLATED GEOMETRIC DISTRIBUTION - Dubey, Akhilesh; Rao, Arun; Pandey, Himanshu (International Journal of Research -GRANTHAALAYAH, 2020)
In this paper Bayes estimators of parameters of inflated geometric distribution have been obtained by taking joint beta prior. The loss functions used are squared, precautionary and entropy.